Analisis Framing Penetapan Tersangka Hasto Kristiyanto di Media Online Hukumonline.com dan Tempo.Co - Manumayasa, Chandra (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study uses Robert N. Entman's framing model analysis method to identify how the two online media present information and build narratives about the Hasto Kristiyanto case. The results of the study show that the media Tempo.co (Rizki, PDIP Determination of Hasto Kristiyanto Suspect Politicization of Law, 2024) and Hukumonline.com (Yandhwiputra, Hasto Kristiyanto Becomes a Suspect, This is the Trace of His Involvement in the Harun Masiku Case, 2024) have differences in the framing used, which reflects the journalistic approach and ideology of each media.